Film rating and its current challenges in Malaysia and Bangladesh - Islam, Md. Zahidul; Rahman, Md. Mashiur (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Film rating is designed to categories film with regard to its suitability for audiences in term of issues such as sex, violence, substance abuse, profanity or other types of mature content. Ratings typically carry age recommendations. This could be regarded as a form of censorship. The main purpose of this paper is to discuss the legal framework of film rating and current challenges in implementing it. A qualitative research’s method was adopted by gleaning information statutes, case law, articles and books. The research also conducted semi-structured interviews with film directors and members of the Film Censorship Board. The research found that there are some contradicting views regarding film rating between the censors and the film industry players.